Individual Differences in Colour Perception: The Role of Low-Saturated and Complementary Colours in Ambiguous Images. (November 2021) - Jeong, EunYoung; Jeong, In-Ho
Individual differences in colour perception, as evidenced by the popular debate of "The Dress" picture, have garnered additional interest with the popularisation of additional, similar photographs. We investigated which colorimetric characteristics were responsible for individual differences in colour perception. All objects of the controversial photographs are composed of two representative colours, which are low in saturation and are either complementary to each other or reminiscent of complementary colours. Due to these colorimetric characteristics, we suggest that one of the two complementary pixel clusters should be estimated as the illuminant hue depending on assumed brightness. Thus, people perceive the object's colours as being biased toward complementarily different colour directions and perceive different pixel clusters as chromatic and achromatic. Even though the distance between colours that people perceive differently is small in colour space, people perceive the object's colour as differently categorized colours in these ambiguous photographs, thereby causing debate. We suggest that people perceive the object's colours using different "modes of colour appearance" between surface-colour and self-luminous modes.